Perinatal out come of Breech Presentation in the Presentation in the Pretext Mode of Delivery - Alnakash, Abdulrazak H. (AL-Kindy College Medical Journal, 2007)
Objectives: To choose the best mode of delivery for term, frank or complete, breech presentation through studying the perinatal outcome of each mode of delivery decided when managing a group of pregnant ladies presented with breech delivery in our centre. Methods: One hundred and fifty pregnant ladies presented at term with singleton, frank or complete, breech presentation for delivery in our centre during the period from May 2004 toAugust 2005. Mode of delivery, parity, gestational age, maternal age, maternal medical illness, and birth weight where the variables that have been tested in each delivery included in the study to verify their relationship to perinatal outcome. Results: No significant relationship is found between the occurrence of adverse perinatal outcome and the variables. However, mode of delivery was the major determinant of the perinatal outcome. of the 150 pregnant ladies, 46 were delivered vaginally, 32 had elective caesarean section, and the remaining 54 pregnant, had undergone an emergency caesarean section because they were presented with labour. Thirteen (8.6 %) babies were adversely affected by the process of delivery, 9 (5%) of them were delivered by vaginal route, 3 (2 %) delivered by emergency caesarean section and one (0.6%) by elective caesarean section. Conclusion: Elective caesarean section is regarded the safest way of delivery for those with term, frank or complete, breech presentation.